Photocurrent Spectroscopy of Perovskite Layers and Solar Cells: A Sensitive Probe of Material Degradation - Holovský, Jakub; De Wolf, Stefaan; Werner, Jérémie; Remeš, Zdeněk; Müller, Martin; Neykova, Neda; Ledinský, Martin; Černá, Ladislava; Hrzina, Pavel; Löper, Philipp; Niesen, Bjoern; Ballif, Christophe (The journal of physical chemistry letters, 2017)
Optical absorptance spectroscopy of polycrystalline CH3NH3PbI3 films usually indicates the presence of a PbI2 phase, either as a preparation residue or due to film degradation, but gives no insight on how this may affect electrical properties. Here, we apply photocurrent spectroscopy to both perovskite solar cells and coplanar-contacted layers at various stages of degradation. In both cases, we find that the presence of a PbI2 phase restricts charge-carrier transport, suggesting that PbI2 encapsulates CH3NH3PbI3 grains. We also find that PbI2 injects holes into the CH3NH3PbI3 grains, increasing the apparent photosensitivity of PbI2. This phenomenon, known as modulation doping, is absent in the photocurrent spectra of solar cells, where holes and electrons have to be collected in pairs. This interpretation provides insights into the photogeneration and carrier transport in dual-phase perovskites.